INFLUENCE OF HEMP SEED PROCESSING PRODUCTS ON STRUCTURAL AND MECHANICAL PROPERTIES OF DOUGH - M. Blazhenko; N. Falendysh (Zernovì Produkti ì Kombìkorma)
The assortment of bread and bakery products on the market of Ukraine mostly has a low nutritional and biological value. Promising raw materials for enriching bread and bakery products are hemp seed processing products, namely hemp flour, hemp protein and kernels. The quality of hemp seed processing products and their influence on the structural and mechanical properties of the dough using these products were investigated. As a result of determining the granulometric composition of hemp protein, it was established that the largest content of 39.55% of particles with a size of 100.0...200.0 microns, at the same time, the diameter of the particles of hemp flour is greater than that of hemp protein and reaches a maximum of 2500 microns. It was established that compared to the control sample, the introduction of hemp processing products reduces the amount of raw gluten from 4.64 to 6.7%, its hydration capacity by 21% to 40%, stretchability, increases its elasticity from 18.4 to 26.5% . The gluten quality of all test samples, depending on the color, elasticity and stretchability, corresponds to the II quality group. As a result of deciphering farinograms, it was established that the stability of dough with hemp flour and protein decreases by 1.5 and 6 minutes, respectively. Alveograms showed that samples with hemp products have a lower extensibility index than the control sample and, accordingly, a higher P/L ratio. The strength of the flour, respectively, is the highest in the control sample, which is 239 a.u., in the samples with the replacement of 10% wheat flour for hemp and 15% wheat flour for hemp protein by 70 and 104 a.u. less than the control. In the course of the study, it was established that the specific volume of the dough and the blurring of the dough ball with the addition of hemp processing products decreases. Based on the results of determining the viscosity of the experimental dough samples, it was found that the control sample has the lowest shear stress, and therefore the lowest viscosity, compared to the samples dough with the introduction of hemp products.